Carbon nanotube buckypaper reinforced polymer composites: A review - Ribeiro, Bruno [UNESP]; Botelho, Edson Cocchieri [UNESP]; Costa, Michelle Leali [UNESP]; Bandeira, Cirlene Fourquet [UNESP] (FapUNIFESP (SciELO), 2017)
This review provides valuable information about the general characteristics, processing conditions and physical properties of carbon nanotube buckypaper (BP) and its polymer composites. Vacuum filtration is the most common technique used for manufacturing BP, since the carbon nanotubes are dispersed in aqueous solution with the aid of surfactant. Previous works have reported that mechanical properties of BP prepared by vacuum filtration technique are relatively weak. On the other hand, the incorporation of polymer materials in those nanostructures revealed a significant improvement in their mechanical behavior, since the impregnation between matrix and BP is optimized. Electrical conductivity of BP/polymer composites can reach values as high as 2000 S/m, which are several orders of magnitude greater than traditional CNT/polymer composites. Also, BP can improve remarkably the thermal stability of polymer matrices, opening new perspectives to use this material in fire retardant applications.
Keywords: BP composites; Carbon nanotubes buckypaper; Physical properties